Changes of antioxidative activities and peptidomic patterns of Auxenochlorella pyrenoidosa protein hydrolysates: Effects of enzymatic hydrolysis and decoloration processes. (December 2021) - Zhang, Wenhan; Jia, Nan; Zhu, Zihao; Wang, Yanchao; Wang, Jingfeng; Xue, Changhu
Abstract: Enzymatic hydrolysis and decoloration are indispensable processes for the production of biological peptides from microalgae materials. Herein, this study aimed to investigate the effects of enzymatic hydrolysis and activated carbon decoloration on antioxidative activities and peptidomic patterns of microalgae protein hydrolysates based on a peptidomic approach. Protein hydrolysates with different hydrolysis time (2–16 h) showed significantly different antioxidative activities based on DPPH and ABTS assays. Regarding the peptidomic pattern, principal component analysis (PCA) models revealed that hydrolysates were classified into discriminable clusters depending on the hydrolysis and decoloration processes. Protein hydrolysates contained many aromatic amino acid containing peptides, such as GDSLYPG, SADPETF, FPALN, FPGDY, and LTDWV, contributing to the classification of PCA models. Activated carbon decoloration at the concentration of 5 mg/mL significantly increased the color lightness by 38.20%, reduced antioxidative activities by 29.78% and 33.59% based on DPPH and ABTS methods, and reduced relative abundances of peptides, especially aromatic amino acid containing peptides. Fifteen selected peptides showed strong ABTS radical scavenging abilities and ten of these peptides were correlated with the antioxidative properties of hydrolysates. The monitoring of dynamic production processes at a molecular scale would contribute to the production and quality control of bioactive peptides from Auxenochlorella pyrenoidosa . Highlights: Antioxidative peptides were prepared from microalgae by hydrolysis and decoloration. Production process of antioxidative peptides was investigated at a molecular scale. Antioxidative activity changed depending on the hydrolysis and decoloration process. PCA models revealed a great differentiation of peptidomic patterns for hydrolysates. Ten peptides were correlated with antioxidative activities of protein hydrolysates.